An Integrative Etic-Emic Approach to Portraying the Halutziut System of Societal Equity: Comparing Israeli Jew and Israeli Arab Perceptions of Justice - Sabbagh, Clara (Journal of cross-cultural psychology, 2005)
Based on equity theory and sociocultural conditions, this study depicts the Israeli system of societal equity from the perspective of the ethos of halutziut (Jewish pioneering).This ethos, which under scores the individual’s contribution to the enhancement of collective goals, has created a correspondence between hierarchically valued signifiers of societal contribution (e.g., military service) and social groupings defined along gender, ethnic, age, and professional lines. This study used multivariate analysis, and Powell’s technique for measuring and spatially portraying respondents’ perceptions of societal equity. Results supported the expected pioneering hierarchy of groupings, mainly among Jewish respondents. Arab respondents differed in their perceptions of groupings associated with Jewish pioneering but were similar regarding other groupings. There is some evidence that perceptions of the contribution and rewards of several groupings, such as social class and gender, may converge across different sociocultural contexts.